MODEL OF IMPROVING ENTREPRENEUR INTENTIONS IN THE CONTEXT OF PARENTAL ROLE - Evita Dewi; Widodo Widodo (IJIBE (International Journal of Islamic Business Ethics), 2017)
The purpose of this study was to describe and analyze the effect of Quality of Education and Risk Taking on Entrepreneur Intentions in the context of Parental Role. The respondents of this study amounted to 300 students of class XII in 3 Vocational High School of SMKN 1 Kudus, SMK Al Islam and SMK NU Banat. Hypothesis testing was conducted using Structural Equation Modeling (SEM) with SmartPLS ver.3 software. The results showed that with Parental Role moderation the total effect of Education Quality and Risk Taking  on Entrepreneur Intentions is smaller than the total effect before moderation, meaning that Parental Role variable does not strengthen the effect of Education Quality - Entrepreneur Intentions and Risk Taking - Entrepreneur Intentions.Keywords: Entrepreneur Intentions, Quality of Education, Risk Taking, Parental Role